The eco-sustainable renovation of knowledge buildings through a cross-border living lab - Antonella Violano; Monica Cannaviello; Souha Ferchichi; Ines Khalifa; Jose Luis Molina; Imad Ibrik; Antonella Trombadore (Techne)
Sustainable building management requires creative interpretation of direct user needs, a skilful balance between technological innovation and applied research into the concept of “Possible Quality”. Med-EcoSuRe research project proposes a pragmatic approach to innovation, whereby experimentation involving the active engagement of end users is conducted with particular focus on human-environment centred design. The objective of this approach is to disseminate effective energy efficiency strategies in university buildings through a cross-border Living Lab. Physical and virtual tools were implemented to foster dialogue and collaboration between academics, decision-makers and stakeholders, and to support university energy managers in planning and implementing innovative energy measures. This paper, starting from a rapid illustration of the results of the research project, illustrates the value enhancing actions post-closure of the project, in progress and/or planned.